Search for the Λ0b → Λη′ and Λ0b → Λη decays with the LHCb detector - Aaij, Roel; Aquines Gutiérrez, Osvaldo; D'Argent, Philippe; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; Färber, Christian; et al. (Journal of high energy physics, 2015)
A search is performed for the as yet unobserved baryonic Λb0 → Λη ′ and Λb0 → Λη decays with 3 fb−1 of proton-proton collision data recorded by the LHCb experiment. The B0 → Ks0η ′ decay is used as a normalisation channel. No significant signal is observed for the Λb0 → Λη ′ decay. An upper limit is found on the branching fraction of < 3.1 × 10−6 at 90% confidence level. Evidence is seen for the presence of the Λb0 → Λη decay at the level of 3σ significance, with a branching fraction.